2001
DOI: 10.1159/000046310
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Severity of Clinicopathological Parameters and Whole Blood Interferon-α Production Capacity in Active Phase IgA Nephropathy Patients

Abstract: Background/Aims: Patients with IgA nephropathy (IgA-N) are thought to have immune system disorders that frequently result in high serum IgA levels and a relatively high susceptibility to upper respiratory infections. Aims: To clarify the influence of the specific immune response of IgA-N patients on the clinicopathological features of the disease, we measured the whole-blood-producing capacity of interferon-α (IFNα-PC). We then compared these findings with clinical and histopathological parameters, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In our previous studies, we have reported that IFN-α production was somehow decreased in patients with lung cancer, MDS, pulmonary tuberculosis, HIV infection, diabetes mellitus and IgA nephritis [12,13] , suggesting that IFN-α production capacity is impaired by various diseases, including cancer, infections, and metabolic disorder. In addition, periodic measurements of IFN-α production revealed decreased IFN-α production capacities in patients with lung [12] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous studies, we have reported that IFN-α production was somehow decreased in patients with lung cancer, MDS, pulmonary tuberculosis, HIV infection, diabetes mellitus and IgA nephritis [12,13] , suggesting that IFN-α production capacity is impaired by various diseases, including cancer, infections, and metabolic disorder. In addition, periodic measurements of IFN-α production revealed decreased IFN-α production capacities in patients with lung [12] .…”
Section: Discussionmentioning
confidence: 96%
“…Several investigators have discussed the impairment of NK cell function, cytotoxic T lymphocyte (CTL) function and dendritic cell (DC) function in hepatitis C patients [8][9][10][11] . In previous papers, we have reported about the impairment of HVJ induced IFN-α production in whole blood cultures of patients with lung cancer, mylodysplastic syndrome, pulmonary tuberculosis, HIV, diabetes mellitus and IgA nephritis [12,13] . Additionally, we mentioned that IFN-α production in patients with lung cancer gradually decreases with the progress of cancer [12] .…”
Section: Introductionmentioning
confidence: 99%
“…This would be consistent with the documented spectrum of cytokines released by peripheral blood mononuclear cells upon challenge with TLR-7 agonists (2, 34). Interestingly, a survey of the available literature revealed that across a number of studies, a typical maximum response in humans (determined via antiviral bioassays) was ϳ10,000 IU of IFN/ml (17,33,38), and therefore, maximum IFN responses appear not to be grossly different between mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] In addition, based on records from a 17-year follow-up study (data are a part of the 24-year database), a comparison of age-matched healthy individuals and HCV patients revealed that impairment of IFN-α production was likely linked to an increase in the cancer risk. 25 Furthermore, we also showed that IFN-α production decline was not only evident in lung cancer and HCV patients but also evident in patients who developed diabetes mellitus.…”
Section: Key Messagesmentioning
confidence: 99%